The Effect of Supportive Educational Intervention on Anxiety Levels in Preoperative Patients Undergoing Spinal Anesthesia - Muhammad Nurfakhir Aliffarhani; Rully Annisa; Marta Tania Gabriel Ching Cing; Heru Purnawan Jati Wibowo (Jurnal Ilmiah Multidisiplin, 2026)
Surgical treatment is an invasive medical procedure that requires anesthesia to reduce pain caused by surgical incisions. Surgical intervention and anesthesia may act as psychological stressors that increase anxiety in patients before surgery. Preoperative anxiety can negatively affect patient comfort and readiness for surgery. One nonpharmacological approach to reduce anxiety is supportive education, which aims to improve patient understanding through structured teaching, guidance, emotional support, and the creation of a supportive learning environment. Methods: This study used a quantitative approach with a preexperimental one group pretest and posttest design. The study population consisted of patients undergoing surgery with spinal anesthesia at a tertiary military hospital in Purwokerto. Participants were selected using purposive sampling. Anxiety levels were measured using a preoperative anxiety assesment instrument consisting of six statements rated on a five point Likert scale. Results: Statistical analysis using the Wilcoxon signed rank test showed a significant difference in anxiety levels before and after the supportive education intervention, with a negative test statistic value and a probability value below the significant threshold. Conclusion: Supportive education was effective in reducing anxiety levels among patients undergoing surgery with spinal anesthesia.